2003
DOI: 10.21273/jashs.128.3.0291
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature, Photosynthetic Photon Flux Density, and Photoperiod on the Vegetative Growth and Flowering of `Autumn Bliss' Raspberry

Abstract: The effects of temperature, photosynthetic photon flux density (PPFD) and photoperiod on vegetative growth and flowering of the raspberry (Rubus idaeus L.) `Autumn Bliss' were investigated. Increased temperature resulted in an increased rate of vegetative growth and a greater rate of progress to flowering. Optimum temperatures lay in the low to mid 20°C range. Above this the rate of plant development declined. Increased PPFD Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
1
22
0
2
Order By: Relevance
“…Apparently, the American cultivars are of little interest for the cool Nordic climate. These results confirm the previous findings of Carew et al (2003) and with 'Autumn Bliss' and 'Polka', respectively, that flowering and fruit maturation are generally advanced by a high "raising" temperature in annual-fruiting raspberries. A notable exception was 'Autumn Treasure', in which flowering was suppressed and strongly delayed by high pre-flowering temperature.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Apparently, the American cultivars are of little interest for the cool Nordic climate. These results confirm the previous findings of Carew et al (2003) and with 'Autumn Bliss' and 'Polka', respectively, that flowering and fruit maturation are generally advanced by a high "raising" temperature in annual-fruiting raspberries. A notable exception was 'Autumn Treasure', in which flowering was suppressed and strongly delayed by high pre-flowering temperature.…”
Section: Discussionsupporting
confidence: 91%
“…While the biennial-fruiting cultivars are short-day (SD) plants that require temperatures below 15°C for the initiation of flowers (Williams, 1960;Sønsteby and Heide, 2008), the annualfruiting cultivars flower freely at temperatures as high as approx. 27°C (Lockshin and Elfving, 1981;Carew et al, 2003) and even at 30°C ). While Carew et al (2003) found no consistent effect of photoperiod on flowering in 'Autumn Bliss', flowering was consistently and significantly advanced and enhanced by long-days (LD) in cv.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bei den herbsttragenden Himbeersorten (engl. : annualfruiting cultivars oder primocane-fruiting cultivars) ist der Einfluss der Umwelt, d. h. unter anderem der Temperatur, auf Wachstum und Blütenanlage bisher nur unzureichend untersucht (Carew et al 1999(Carew et al , 2003Oliveira u. Dale 2007;Dale 2008). Dennoch ist festzustellen, dass die herbsttragenden Himbeersorten für die Blütenbildung nicht auf so niedrige Temperaturen angewiesen sind wie die sommertragenden Sorten.…”
Section: Himbeerenunclassified
“…Nach Cameron et al (1993) liegt das Temperaturoptimum der Fotosynthese und damit der Kohlenhydratproduktion bei Himbeeren im Bereich von 12-20°C. Nach Carew et al (2003) hat die herbstragenden Sorte 'Autumn Bliss' das beste Rutenwachstum bei 24°C und reagiert mit reduziertem Wachstum bei weiter ansteigenden Temperaturen.…”
Section: Allgemeines Pflanzenwachstumunclassified